О, О‐Dialkyl‐S‐(1, 1‐dimethyl‐2‐oxoethyl)dithiophosphates: Synthesis and Reactions with n‐Nucleophiles. Issue 6 (30th June 2015) - Gazizov, Mukattis B.; Khairullin, Rafail A.; Aksenov, Nikita G.; Sinyashin, Oleg G.
ABSTRACT: Hydrolysis of the new types of iminium salts was used to synthesize О, О ‐dialkyl‐ S ‐(1, 1‐dimethyl‐2‐oxoethyl)dithiophosphates or 2‐dialkoxythiophosphorylthio‐substituted aldehydes with carbon isochain. Reactions of aldehydes with N‐, N, N‐, and O, N‐nucleophiles gave new phosphorylated imines containing an acetal group at different positions, perhydro‐1, 3‐diazol and oxazol with the diisopropoxythiophosphorylthio group in a side chain, and hydrazone of this aldehyde and diphenylphosphinylacetic acid hydrazide.